Investigation of linearity of the ITER outer vessel steady-state magnetic field sensors at high temperature. (5th July 2017) - Entler, S.; Duran, I.; Kocan, M.; Vayakis, G.
Abstract: Three vacuum vessel sectors in ITER will be instrumented by the outer vessel steady-state magnetic field sensors. Each sensor unit features a pair of metallic Hall sensors with a sensing layer made of bismuth to measure tangential and normal components of the local magnetic field. The influence of temperature and magnetic field on the Hall coefficient was tested for the temperature range from 25 to 250 ̂ C and the magnetic field range from 0 to 0.5 T. A fit of the Hall coefficient normalized temperature function independent of magnetic field was found, and a model of the Hall coefficient functional dependence at a wide range of temperature and magnetic field was built with the purpose to simplify the calibration procedure.